2016
DOI: 10.21512/lc.v10i2.898
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Collaborative Writing Strategy (CWS) in Writing Lesson Regarded to The Students’ Creativity

Abstract: This study is aimed at finding out what appropriate methods to be usedin writing lesson seen from the students’ creativity especially for studentswho have high creativityand low creativity. This study used quasi experimental research. The population of the research was the eighth grade of a Junior High School in Wonosari in the academic year of 2013/2014. The sampling technique used was cluster random sampling. The sample in this study was 64 students covering 32 students of E as experimental class and 32 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
3
12
2
1
Order By: Relevance
“…In line with the previous explanation, it can be stated that good ability of the students in writing argumentative essays was basically influenced by the students' good ability in applying the Collaborative Writing strategy. This research result was in line with previous research conducted by Abbas, Fachrurrazy, & Wahjudi (2013), Zuhri (2009), Wahyuni (2017), Soraya (2016), and Lestari, Setyowati, Sukmawan, and Latief (2017) about the implementation of collaborative writing strategy in improving the students' writing skill. Based on the results of this research, it was proven that the implementation of the collaborative writing strategy in the learning process could improve the students' skill in writing.…”
Section: Diagram 4 the Students' Mid-term Test Results Per Assessmensupporting
confidence: 91%
“…In line with the previous explanation, it can be stated that good ability of the students in writing argumentative essays was basically influenced by the students' good ability in applying the Collaborative Writing strategy. This research result was in line with previous research conducted by Abbas, Fachrurrazy, & Wahjudi (2013), Zuhri (2009), Wahyuni (2017), Soraya (2016), and Lestari, Setyowati, Sukmawan, and Latief (2017) about the implementation of collaborative writing strategy in improving the students' writing skill. Based on the results of this research, it was proven that the implementation of the collaborative writing strategy in the learning process could improve the students' skill in writing.…”
Section: Diagram 4 the Students' Mid-term Test Results Per Assessmensupporting
confidence: 91%
“…This research already answers the research questions by data. The result of this study was relevant with the previous studies conducted by Talib and Cheung (2017), Soraya (2016), and Deveci (2018) in which the result of their study showed that by using Collaborative technique in teaching writing can give students opportunities to use language with their own way and style.…”
Section: Resultssupporting
confidence: 82%
“…CWS is able to give many advantages and can be confirmed as an effective writing strategy. It was in line with Soraya's (2016) and Abbas & Herdi' studies (2018). Based on the results of this research, it was proven that the implementation of CWS in the learning process could improve the students' writing ability.…”
Section: Table 1 Descriptive Statisticssupporting
confidence: 91%